An Update of Nucleic Acids Aptamers Theranostic Integration with CRISPR/Cas Technology - Mina Roueinfar; Hayley N. Templeton; Julietta A. Sheng; Ka Lok Hong (Molecules, 2022)
The clustered regularly interspaced short palindromic repeat (CRISPR)/Cas system is best known for its role in genomic editing. It has also demonstrated great potential in nucleic acid biosensing. However, the specificity limitation in CRISPR/Cas has created a hurdle for its advancement. More recently, nucleic acid aptamers known for their high affinity and specificity properties for their targets have been integrated into CRISPR/Cas systems. This review article gives a brief overview of the aptamer and CRISPR/Cas technology and provides an updated summary and discussion on how the two distinctive nucleic acid technologies are being integrated into modern diagnostic and therapeutic applications